Job Motivation and Satisfaction Among Furniture Factory Workers in Lalitpur - Acharya, Min Raj; Joshi, Bishnu Maya (Ganeshman Darpan, 2026)
Motivation can affect not only the acquisition of people’s skill and abilities but also how and to what extent they utilize their skill and abilities. Work Motivation has been of interest to industrial & organizational psychologists at least science the 1930s, stimulated in large part by the famous Hawthorne studies. This study analyzes the role of job rotation in improving employee performance through job satisfaction and motivation. Theoretically, this research is expected to make academic contributions in the field of human resource management. We employed qualitative research paradigm followed by basic qualitative research design to examine job motivation and satisfaction among the furniture workers in this study. This study found the confidence in craftsmanship and the financial independence that comes with having a specialized skill drive the resilient group of Lalitpur’s furniture workers. For employees like Respondent, their work is a profession of status and respect rather than one of survival.